A nationwide retrospective study in Turkish children with nephrocalcinosis - ALPAY, HARİKA; GÖKCE, İBRAHİM (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2021)
Background/aim: Nephrocalcinosis (NC) is defined as calcium deposition in the kidney parenchyma and tubules. This study aims to determine the etiology, risk factors, and follow-up results of patients with NC in Turkey. Materials and methods: Patients diagnosed with NC in the pediatric nephrology Department Units of 19 centers from all geographical regions of Turkey over a 10-year period (2010-2019) were included in the study. The medical records from the centers were reviewed and demographic data, admission complaints, medical history, systemic and genetic disorders, risk factors for NC, treatment details, and presence of NC after one-year follow-up, were recorded retrospectively. Results: The study sample included 195 patients (88 females, 107 males). The mean age at diagnosis was 39.44 +/- 47.25 (0.5-208) months; 82/190 patients (43.2%) were diagnosed incidentally; 46/195 patients (23.6%) had an underlying disease; idiopathic hypercalciuria was detected in 75/195 (38.4%) patients. The most common systemic diseases were distal renal tubular acidosis in 11/46 patients (23.9%), primary hyperoxaluria in 9/46 patients (19.6%) and Bartter syndrome in 7/46 patients (15.3%). After one year of follow-up, NC resolved in 56/159 patients (35.2%) and they all did not have an underlying systemic disease. Conclusion: The most common presentation of NC was incidental. Distal renal tubular acidosis and primary hyperoxaluria were the main systemic diseases leading to NC, while hypercalciuria was the most common metabolic risk factor. Nephrocalcinosis was found to remain in most of the patients at a one-year follow-up. It may resolve particularly in patients with no underlying systemic disease.
Keywords: Bartter syndrome; hypercalciuria; nephrocalcinosis; renal tubular acidosis